2023
DOI: 10.1021/acsbiomaterials.2c01566
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Profiling of the Extracellular Matrix and Integrins Expressed by Human Corneal Endothelial Cells Cultured on Silk Fibroin-Based Matrices

Abstract: Developing a scaffold for culturing human corneal endothelial (HCE) cells is crucial as an alternative cell therapeutic approach to bridge the growing gap between the demand and availability of healthy donor corneas for transplantation. Silk films are promising substrates for the culture of these cells; however, their tensile strength is several-fold greater than the native basement membrane which can possibly influence the dynamics of cell–matrix interaction and the extracellular matrix (ECM) secreted by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…SF-based matrices have been fabricated to engineer tissues like bone, cartilage, blood vessels, meniscus, heart, intervertebral discs, liver and skin for accessing the in vitro and in vivo tissue-specific responses [21,79,83,84,86,91,92,[94][95][96][97][98][99][100][101][102] (figure 2). SF-based matrices have been extensively evaluated for cartilage regeneration.…”
Section: Silk As a Biomaterialsmentioning
confidence: 99%
“…SF-based matrices have been fabricated to engineer tissues like bone, cartilage, blood vessels, meniscus, heart, intervertebral discs, liver and skin for accessing the in vitro and in vivo tissue-specific responses [21,79,83,84,86,91,92,[94][95][96][97][98][99][100][101][102] (figure 2). SF-based matrices have been extensively evaluated for cartilage regeneration.…”
Section: Silk As a Biomaterialsmentioning
confidence: 99%
“…Silk has also been used in an in vivo rabbit model and could recover corneal transparency over a 6-week follow-up period ( Vazquez et al, 2017 ). Furthermore, Hazra et al demonstrated that despite the much greater tensile strength of silk membrane compared to native Descemet’s membrane, human CECs secreted similar ECM proteins and exhibited endothelial phenotype in long-term cell culture ( Hazra et al, 2023 ). Long-term in vivo studies are still needed to evaluate safety and performance.…”
Section: Tissue Engineering Of the Corneal Endotheliummentioning
confidence: 99%